2015
DOI: 10.1094/pdis-09-14-0926-re
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Populations of ‘Candidatus Liberibacter asiaticus’ in Citrus Trees in Paraná State, Brazil

Abstract: Sauer, A.V., Zanutto, C.A., Nocchi, P.T.R., Machado, M.A., Bock, C.H, and Nunes, W.M.C. 201X. Seasonal variation in populations of 'Candidatus Liberibacter asiaticus' in citrus trees in Paraná state, Brazil. Plant Disease XX: xx-xx.Huanglongbing (HLB) is considered one of the most destructive diseases of citrus as the plants rapidly become unproductive, enter a decline and eventually die. HLB is caused by the phloem-limited bacterium 'Candidatus Liberibacter' spp. The objective of this study was to evaluate se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 33 publications
(65 reference statements)
0
16
0
2
Order By: Relevance
“…The influence of environmental conditions on the transmission of CLas and CLam is little known, but there is a marked effect on the populations of these bacteria in the host plant. Some authors have reported that CLas is affected by high temperatures (between 24 and 38°C), leading to reduced bacterial titer in plants (Lopes et al 2009b;Gasparoto et al 2012;Sauer et al 2015) and in insect vectors that fed on infected plants (Lopes et al 2013). Water deficit also negatively affected CLas populations in young shoots of citrus plants (Lopes et al 2017).…”
Section: Factors Influencing Transmissionmentioning
confidence: 99%
“…The influence of environmental conditions on the transmission of CLas and CLam is little known, but there is a marked effect on the populations of these bacteria in the host plant. Some authors have reported that CLas is affected by high temperatures (between 24 and 38°C), leading to reduced bacterial titer in plants (Lopes et al 2009b;Gasparoto et al 2012;Sauer et al 2015) and in insect vectors that fed on infected plants (Lopes et al 2013). Water deficit also negatively affected CLas populations in young shoots of citrus plants (Lopes et al 2017).…”
Section: Factors Influencing Transmissionmentioning
confidence: 99%
“…Such qPCR negative results are typical for hot summer months, as the bacteria clears in the shoots due to high temperatures, which were in the range of 100-120 °F during May-August. Although well-documented, this problem substantially complicates qPCR-based diagnostics of HLB [31][32][33][34] . The Raman readings, however, reported stable signal intensity of 1610 cm −1 band above 1.925 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…C Las also is more abundant and more consistently detectable, in roots than in shoots, making root a preferred source tissue in which to perform disease diagnostics tests. Furthermore, roots act as the reservoir for C Las between periods of foliar flushing 86 and to endure the seasonal fluctuations of high temperatures in summer months 84 . Relatively few groups have studied C Lso root infections, but the levels and distribution of C Lso are greater in roots than shoots, much as for C Las 91 .…”
Section: Discussionmentioning
confidence: 99%
“…A salient feature of the microbial hairy root system is that the efficacy assays are conducted in living (root) tissues that not only mimic the native environment of the pathogen but also encompass features that underpin native plant-microbe interactions, aspects that cannot be replicated in axenic culturing systems. A growing number of studies have indicated the pivotal roles of roots, root-rhizosphere interactions and root-microbiome composition in plant health and disease, including citrus health and HLB progression [84][85][86][87][88][89][90] . For instance, in the majority of presymptomatic citrus trees, roots appear to be the first site of CLas detection, preceding leaves 86 .…”
Section: Clso-potato Hairy Rootsmentioning
confidence: 99%